Enteral immunonutrition versus enteral nutrition for gastric cancer patients undergoing a total gastrectomy: a systematic review and meta-analysis - Cheng, Ying (BMC Gastroenterol, 2018)
BACKGROUND: Nutrition support is a common means for patients with gastric cancer, especially for those undergoing elective surgery. Recently, enteral immunonutrition (EIN) was increasingly found to be more effective than enteral nutrition (EN) in enhancing the host immunity and eventually improving the prognosis of gastric cancer patients undergoing gastrectomy. However, the results reported were not consistent. This meta-analysis aimed to assess the impact of EIN for patients with GC on biochemical, immune indices and clinical outcomes. METHODS: Four electronical databases (Medline, EMBASE, Scopus and Cochrane library) were used to search articles in peer-reviewed, English-language journals. Mean difference (MD), Relative risk (RR), or standard mean difference (SMD) with 95% confidence interval (CI) were calculated. Heterogeneity was assessed by Cochrane Q and I(2) statistic combined with corresponding P-value. The analysis was carried out with RevMan 5.3. RESULTS: Seven studies involving 583 patients were eligible for the pooled analysis. EIN, when beyond a 7-day time-frame post-operatively (D ≥ 7), increased level of CD4(+) (SMD = 0.99; 95% CI, 0.65–1.33; P < 0.00001), CD4(+)/ CD8(+) (SMD = 0.34; 95% CI, 0.02–0.67; P = 0.04), the IgM (SMD = 1.15; 95% CI, 0.11–2.20; P = 0.03), the IgG (SMD = 0.98; 95% CI, 0.55–1.42; P < 0.0001), the lymphocyte (SMD = 0.69; 95% CI, 0.32–1.06; P = 0.0003), and the proalbumin (SMD = 0.73; 95% CI, 0.33–1.14; P = 0.0004). However, those increased effects were not obvious within a 7-day time-frame post-operatively (D < 7). The levels of CD8(+) and other serum proteins except proalbumin were not improved both on D ≥ 7 and D < 7. Clinical outcomes such as systemic inflammatory response syndrone (SIRS) (MD, - 0.89 days; 95% CI, - 1.40 to - 0.39; P = 0.005), and postoperative complications (RR, 0.29; 95% CI, 0.14–0.60; P = 0.001) were significantly reduced in EIN group. Pulmonary infection and length of hospitalization (LHS) were not improved no matter what time after surgery. CONCLUSIONS: EIN was found to improve the cellular immunity, modulate inflammatory reaction and reduce postoperative complication for GC patients undergoing radical gastrointestinal surgery. Exclusion of grey literature and non-English language studies was the key limitation in this study.